1993
DOI: 10.1159/000129276
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Small Bowel Grafts – A Comparison with Two Standard Solutions

Abstract: This study investigates the use of EuroCollins (EC) and University of Wisconsin (UW) solution, two major preservation fluids, for small bowel preservation. After in situ flushing, grafts were cold-stored at 4°C with either EC for 30 min (group 1a), 6 h (group 1b) and 12 h (group 1c) or with UW for 30 min (group 2a), 6 h (group 2b) and 12 h (group 2c). Using UW, cold ischemia was extended to up to 18 h (group 2d). As a control, small intestines were flushed and stored for the same time periods in cold saline (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Although the sensitivity of the small intestine to warm and cold ischemia has been well studied by morphology and biochemistry [6–10], only a few reports have examined the colon after warm ischemia [11–14]. In a canine model employing the Ussing chamber method, we concluded that the colon was more resistant to ischemic insult than the small bowel [15].…”
mentioning
confidence: 79%
“…Although the sensitivity of the small intestine to warm and cold ischemia has been well studied by morphology and biochemistry [6–10], only a few reports have examined the colon after warm ischemia [11–14]. In a canine model employing the Ussing chamber method, we concluded that the colon was more resistant to ischemic insult than the small bowel [15].…”
mentioning
confidence: 79%
“…The use of UWM for the small bowel is less effective than for other organs such as the kidney, liver and pancreas (18). According to published experimental data, no currently available preservation solution could give consistent results after 24 h of small bowel preservation, although only a few studies have reported the recipient survival and graft function after preservation in a large animal model (18)(19)(20)(21)(22). Therefore, developing a more potent technique to extend the preservation time is essential for increasing the donor pool, thereby allowing more time for recipient preparation and improving patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A safe time period for small bowel preservation using UW solution is currently 10-12 h [18]. Because of the ineffectiveness of saline as a small bowel preservation solution after 6 h of cold ischemia [19], the measured values of the chosen parameters in groups with no cold ischemia were taken as control values.…”
Section: Discussionmentioning
confidence: 99%